The Effect of Inflation, Exchange Rates, and Interest Rates on Stock Returns in Mining Sector Companies Listed on the Indonesia Stock Exchange for the 2022-2024 Period - Nofitasari, Susi (Westscience Press, 2025)
This study aims to analyze the effect of inflation, exchange rates, and interest rates on stock returns in the mining sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The data used in this research is secondary data, including financial reports, inflation rates, exchange rates, and interest rates obtained from official sources such as the Indonesia Stock Exchange and Bank Indonesia. The analysis method employed is multiple linear regression using SPSS software. The results indicate that, partially, inflation and exchange rates have a negative and significant effect on stock returns, while interest rates have a negative but not significant effect. Simultaneously, inflation, exchange rates, and interest rates significantly influence stock returns. The Adjusted R-Square value of 0.211 suggests that the independent variables in this study explain 21.1% of the variation in stock returns, with the remaining percentage influenced by other factors outside the research model. This study implies that investors should consider inflation, exchange rate fluctuations, and interest rate movements when making investment decisions. Furthermore, the findings serve as a reference for future research on the impact of macroeconomic factors on stock market performance.